(untitled) (Docentes 2.0 Journal, 2025)
The globe’s environmental problems have worsened over the past two centuries; the consequences demonstrate that ecosystems on land and in the oceans are collapsing, causing irreversible damage. The research aimed to explore the implementation of educational archetypes to promote global citizenship within an environmental culture paradigm, which is essential for fostering care for natural resources. The investigation employed a transdisciplinary methodology based on the pragmatic paradigm, an inductive approach, a mixed-methods design, an exploratory, documentary-style design, and a longitudinal section. It allowed for the integration of knowledge from disciplines to access the complexity of the social reality in which we live. The socioeconomic systems of sovereignties acquire a prototype to create sustainable horizons. Within the framework of the Sustainable Development Goals for 2030, this includes a perspective for green education. The framework for action involves practicing at the regional level and proposing strategies that consider realities and capacities at each stage of development. Today, citizens are involved in environmental issues; it is up to education to undertake a global educational crusade. A commitment to sustainability in the development of human values, duties, and rights helps ensure individual, community, and environmental well-being. Looking ahead, according to UNESCO, key priorities include gender equality, the promotion of a culture of peace, the acceptance of cultural diversity as a factor in humanity’s uniqueness, and a culture of sustainable well-being.